Assessment of remnant liver function and volume after selective ligation of portal vein and hepatic artery in a rat model - Abreu,Thiago Boechat de (2019)
Abstract Purpose: To evaluate liver regeneration after selective ligation of portal vein and hepatic artery by 3D Computed Tomography in an experimental model. Methods: Sixteen Wistar rats were randomized into four equal groups: Group I- control (sham), Group II- isolated selective ligation of the hepatic artery, Group III- isolated selective ligation of the portal vein and Group IV- combined ligation of portal vein and hepatic artery. Before procedure and five days after a 3D CT Scan was performed to analyze the hypertrophy, weight and function of the remnant liver. Results: The largest regeneration rate and increase of weight in the hypertrophied lobe was detected in group IV, the first with an average of 3.99 (p=0.006) and the last varying from 6.10g to 9.64g (p=0.01). However, total liver weight and the R1 ratio (Hypertrophied Lobe Weight/Total Liver Weight) was higher in group III (P<0.001) when compared with groups I, II and IV and showed no difference between them. The immunohistochemical examination with PCNA also found higher percentages with statistical significance differences in rats of groups III and IV. It was possible to confirm a strong correlation between hypertrophied lobe weight and its imaging volumetric study. Liver function tests only showed a significant difference in serum gamma-glutamyltransferase and phosphorous. Conclusion: There is a largest liver regeneration after combined ligation of portal vein and hepatic artery and this evidence may improve the knowledge of surgical treatment of liver injuries, with a translational impact in anima nobile.